Media communication and regional news. Public television in Rio Negro - Schleifer, Pablo (2018)
The objective of the present article is to understand the meaning of communication policies regarding the state television channel by the governments of the province Rio Negro since the end of the Transition Union of Companies with Artear until 2015. In effect, in 2009 this link is terminated and a process of re-nacionalization of the station begins which will highlight the tensions between the constitution of a public service or the government´s use of the only air television channel. In this context, we analyze these policies according to three dimensions: the constitution of the control and management organs, the programming and the financing.